Agile Marketing and Its Role in Achieving Competitive Advantage in Companies : An Applied Study on Food Companies in Iraq - Hussein , Sajjad K. (PROSPECTIVE RESEARCHES, 2026)
This study examines the extent to which food companies in Iraq adopt agile marketing and its role in achieving competitive advantage in a highly dynamic and competitive market. It also analyzes the availability of agile marketing dimensions and their impact on enhancing companies’ responsiveness to market demands and strengthening their competitive position. The study adopts a descriptive-analytical approach, using a questionnaire as the primary data collection tool, with data analyzed through appropriate statistical methods. The results revealed that the company under study has a clearly positive orientation toward adopting agile marketing, with its dimensions being available at a high level. The most prominent dimensions were robustness, proactiveness, market sensing, rapid responsiveness, and flexibility. The findings also showed that the company achieves a high level of competitive advantage, represented mainly by differentiation, cost leadership, quality, and focus on competition. Statistical analysis confirmed the existence of a positive and significant effect of agile marketing on achieving competitive advantage, reflecting the importance of this approach in improving marketing performance. Based on these results, the study proposed several recommendations, most notably strengthening continuous market research, improving quality standards, monitoring prices in line with customer needs, enhancing marketing strategies, and reinforcing communication channels with customers to achieve sustainable competitiveness.